2018
DOI: 10.1108/k-04-2017-0139
|View full text |Cite
|
Sign up to set email alerts
|

The optimal thermal causal path analysis on the relationship between international crude oil price and stock market

Abstract: Purpose The purpose of this study is to reveal the lead–lag structure between international crude oil price and stock markets. Design/methodology/approach The methods used for this study are as follows: empirical mode decomposition; shift-window-based Pearson coefficient and thermal causal path method. Findings The fluctuation characteristic of Chinese stock market before 2010 is very similar to international crude oil prices. After 2010, their fluctuation patterns are significantly different from each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Singh and Sharma (2018) estimated the dynamic relationship between gold, crude oil, US dollar, exchange rate and Sensex and found a long-run relationship between crude oil and Sensex. Another study was conducted on GCC countries by (Yao et al, 2018) where the authors studied the lead-lag structure between the oil price and stock market. A similar study was conducted on GCC countries to find out the degree of dependence between crude oil and equity markets (Mokni and Yousseff, 2019) and found there is a positive influence of crude prices on equity markets of GCC countries with a high degree of dependence on Saudi Arabia equity market.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Singh and Sharma (2018) estimated the dynamic relationship between gold, crude oil, US dollar, exchange rate and Sensex and found a long-run relationship between crude oil and Sensex. Another study was conducted on GCC countries by (Yao et al, 2018) where the authors studied the lead-lag structure between the oil price and stock market. A similar study was conducted on GCC countries to find out the degree of dependence between crude oil and equity markets (Mokni and Yousseff, 2019) and found there is a positive influence of crude prices on equity markets of GCC countries with a high degree of dependence on Saudi Arabia equity market.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Wen et al (2020) found that there exists upside and downside risk spillover effects that are stronger from exchange rates to crude oil than those from oil to exchange rate markets. Yao et al (2018) show that the stock markets significantly led international crude oil prices, revealing varying leadlag orders among stock markets. Zhang & Wu (2018) found significant bidirectional linear causality between WTI crude oil returns and China's traditional energy sectoral stock returns, but the nonlinear causality appears weaker, and the influence of WTI crude oil returns on traditional energy sectoral stock returns has time-varying characteristics and industry heterogeneity both in the linear and nonlinear cases, and finally, the decline of WTI crude oil prices may strengthen its linear influence on the stock returns of traditional energy sectors, while the excessive rise of market values in traditional energy sectors may weaken the linear and nonlinear influence of WTI on them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Peng et al (2018) found a noteworthy spillover of crude-oil risk to Chinese firms. Yao et al (2018) noticed that the Chinese financial market presented a leading effect on crude-oil price from 2000 to 2004. Yin and Feng (2019) indicated that investor's attention to oil presents prediction ability of the US stock market returns.…”
Section: Literature Reviewmentioning
confidence: 99%